Pemberdayaan Pemuda dan Jemaat dalam Pelayanan Gereja: Strategi Penguatan Kepemimpinan di GKSI Ampadi - Marni Marni; Ester Novita Desi (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2025)
This community service activity aims to strengthen the leadership capacity of youth and congregations at the Faithful Christian Church of Indonesia (GKSI) Ampadi, West Kalimantan, through empowerment programs and training based on spiritual values. The church as a faith community has a strategic responsibility in creating leadership regeneration, but the reality on the ground shows that youth involvement in ministry is still limited. This service activity was carried out with a participatory and qualitative descriptive approach, through stages of observation, literature study, spiritual leadership training, cross-generational mentoring, and direct assistance to participants. The results of the activity showed that the low participation of youth in GKSI Ampadi was caused by a lack of structural development, the dominance of the senior generation, and the absence of a clear cadre system. Through a Bible-based leadership training program, the formation of an inclusive ministry team, and ongoing mentoring, there was a significant increase in youth involvement and synergy between congregations. In addition, this activity produced a leadership cadre roadmap as a strategic guide for the church in developing human resources for ministry. This service activity not only had an impact on improving the quality of service and congregational activity, but also strengthened the process of sustainable leadership regeneration within the local church environment. It is hoped that this empowerment model can be applied contextually by other churches to build dynamic, inclusive, and contemporary service communities.